Expression of Drosophila virilis Retroelements and Role of Small RNAs in Their Intrastrain Transposition - Rozhkov, Nikolay V. (Public Library of Science, 2011)
Transposition of two retroelements (Ulysses and Penelope) mobilized in the course of hybrid dysgenesis in Drosophila virilis has been investigated by in situ hybridization on polytene chromosomes in two D. virilis strains of different cytotypes routinely used to get dysgenic progeny. The analysis has been repeatedly performed over the last two decades, and has revealed transpositions of Penelope in one of the strains, while, in the other strain, the LTR-containing element Ulysses was found to be transpositionally active. The gypsy retroelement, which has been previously shown to be transpositionally inactive in D. virilis strains, was also included in the analysis. Whole mount is situ hybridization with the ovaries revealed different subcellular distribution of the transposable elements transcripts in the strains studied. Ulysses transpositions occur only in the strain where antisense piRNAs homologous to this TE are virtually absent and the ping-pong amplification loop apparently does not take place. On the other hand small RNAs homologous to Penelope found in the other strain, belong predominantly to the siRNA category (21nt), and consist of sense and antisense species observed in approximately equal proportion. The number of Penelope copies in the latter strain has significantly increased during the last decades, probably because Penelope-derived siRNAs are not maternally inherited, while the low level of Penelope-piRNAs, which are faithfully transmitted from mother to the embryo, is not sufficient to silence this element completely. Therefore, we speculate that intrastrain transposition of the three retroelements studied is controlled predominantly at the post-transcriptional level.